Influence of Group Identification on Malicious and Benign Envy: A Cross-Sectional Developmental Study - Gaviria, Elena; Quintanilla, Laura; Navas, María José (Frontiers in Psychology, 2021)
Envy is the result of a social comparison that shows us a negative image of ourselves. The present study addresses the effect of the context of group comparison and group identification on children’s expression of this emotion. Through different stories, participants aged between 6 and 11 years were exposed to four contexts of upward social comparison in which they had to adopt the role of the disadvantaged character. From their emotional responses and their decisions in a resource allocation task, three response profiles were created: malicious envy, benign envy, and non-envy. Although we found important differences between verbal and behavioral responses, the results showed greater envy, both malicious and benign, when the envied was an out-group. On the other hand, when the envied belonged to the in-group and competed with a member of the out-group, malicious but not benign envy practically disappeared. With age, envious responses decreased and non-envious responses increased. The role of social identity in the promotion and inhibition of envy is discussed, as well as the acquisition of emotional display rules in the benign envy and non-envy profiles.